2014
DOI: 10.1097/ajp.0b013e318287a2a4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Pain Responses Support Peripheral and Central Sensitization in Patients With Unilateral Shoulder Pain

Abstract: Objective The aims of this study were to 1) examine the pattern of experimental pain responses in the affected and non-affected extremities in patients with shoulder pain and 2) explore the intra-individual association between sensitization states derived from experimental pain testing. Methods Experimental pain responses from 58 patients with shoulder pain (17 females, ages 18 to 52) were compared to those from 56 age- and sex-matched healthy volunteers (16 females, ages 21 to 58). Experimental pain respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 52 publications
1
110
4
1
Order By: Relevance
“…The presence of central and peripheral sensitization mechanisms as responsible for the changes of mechanical pain sensitivity observed in unilateral shoulder pain has been previously reported (Coronado et al, 2011(Coronado et al, , 2014. Some authors suggest changes in central (Hidalgo-Lozano et al, 2010;Paul et al, 2012) and peripheral (Alburquerque-Sendín et al, 2013) nervous systems in individuals with unilateral SAPS.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The presence of central and peripheral sensitization mechanisms as responsible for the changes of mechanical pain sensitivity observed in unilateral shoulder pain has been previously reported (Coronado et al, 2011(Coronado et al, , 2014. Some authors suggest changes in central (Hidalgo-Lozano et al, 2010;Paul et al, 2012) and peripheral (Alburquerque-Sendín et al, 2013) nervous systems in individuals with unilateral SAPS.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, increased mechanical sensitivity can also occur on the nonaffected side as a sign of central sensitization . Although bilateral hyperalgesia has already been identified in unilateral shoulder pain (Hidalgo-Lozano et al, 2010;Paul et al, 2012;Coronado et al, 2014;Sanchis et al, 2015), results are still conflicting which increases the interest of research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated increased sensitivity to mechanical stimulation and receptive field expansion in dorsal horn neurons following injection of bradykinen into the lumbar multifidus [69,70]. By recording pain threshold following repeated stimuli to peripheral C-fibers, a number of studies have also reported wind-up related, central sensitization in patients with low back pain [71][72][73] TMJ pain [74] shoulder pain [75] and fibromyalgia [76]. Subacute or chronic C-fiber mediated pain increases the release of glutamate and substance-P from sensory afferents in spine, leading to hypersensitivity of second order, dorsal horn neurons.…”
Section: The Transition Of Peripheral Pain To Central-mediated Chronimentioning
confidence: 99%
“…Characterizing mechanisms and outcomes following multiple doses would more closely mirror clinical practice and may yield different results. We also did not assess subjects enrolling into this study for peripheral or central sensitization to pain, and prior research (Coronado et al, 2014) suggests that there may be a heterogeneous mix of patients with shoulder pain exhibiting peripheral and/or central pain sensitization.…”
Section: Limitationsmentioning
confidence: 99%